Comunicação cooperativa com codificação de rede e alocação de subportadoras - Ton, Thiago Henrique (2017)
In this master’s thesis a new model for network-coded cooperative communication in orthogonal frequency division multiple access (OFDMA) scenarios is proposed. The proposed model is an extension of the Generalized Dynamic Network Coding (GDNC), incorporating into it a subcarrier allocation method provided by the maximum-constraint matching allocation (MCMA) algorithm. The objective is to provide GDNC with the ability to explore frequency diversity through proper subcarrier allocation for the nodes in the system. The analysis of the proposed model, GDNC-OFDMA, is developed in scenarios in which coherence blocks undergo Rayleigh fading. Equations for outage probability of the system, as well as the diversity-multiplexing trade-off (DMT) are obtained and compared with numerical simulations. The performance of GDNC-OFDMA is compared with an analogous scheme which also explores frequency diversity in the same manner, the NCC-OFDMA, which is reviewed in this work in order to obtain a more realistic version compared to the one originally proposed. Results showed that GDNCOFDMA surpasses GDNC in terms of diversity at the cost of a decreasing in multiplexing rate, being preferable its adoption in applicable scenarios rather than the original version. Moreover, GDNC-OFDMA has better performance in terms of outage probability and diversity when compared to NCC-OFDMA.